PEMILIHAN KRITERIA DALAM PEMBUATAN KARTU KREDIT DENGAN MENGGUNAKAN METODE FUZZY AHP - APRIANTO, JOKO HADI; GANDHIADI, G. K.; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2014)
The rise of credit card users, make banks compete to provide a wide range of offers to attract customers. This study aims to determine the priority criteria selected customers for establishment credit cards by using a fuzzy AHP method. Method fuzzy AHP is a combination of the AHP method and fuzzy method. Fuzzy AHP approach particularly triangular fuzzy number approach to the AHP scale should be able to minimize uncertainty for the results obtained are more accurate. The criteria used for this study is the interest rate , the promo/discount, limit, and annual dues. Based on the steps of calculation of data obtained fuzzy AHP respondents have value CR = 0.049, which means consistent because it meets the standards set CR < 0.10 and that became the order of priority are limit, promo/discount, interest rate, and  continued with weights of priorities are 0408, 0.28, 0.16, and 0.152.
Keywords: AHP; Fuzzy Analytic Hierarchy Process (FAHP); Criteria of Credit Card; Consistensy Ratio; Weight Priority